2019
DOI: 10.3389/fimmu.2019.00393
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Effects on Diurnal Rhythms in Cell Numbers of Peripheral Leukocytes in Domestic Pigs

Abstract: The photoperiod is known to modulate immune cell number and function and is regarded essential for seasonal disease susceptibility. In addition, diurnal variations in the immune system are regarded important for immune competence. Whereas few studies investigated the influence of season, none investigated the specific effect of the photoperiod on these diurnal immune rhythms until now. Therefore, the present study compared diurnal rhythms in cell numbers of peripheral leukocyte types in domestic pigs held eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…During the CTRL period, the investigated leukocyte subsets were similar to previous studies regarding numbers and diurnal pattern (11,32,33). In the stress hormone phase, all of the applied hormones caused changes in the number of distinct leukocyte subsets, as illustrated in Fig.…”
Section: Leukocyte Numbers and Subsetssupporting
confidence: 84%
“…During the CTRL period, the investigated leukocyte subsets were similar to previous studies regarding numbers and diurnal pattern (11,32,33). In the stress hormone phase, all of the applied hormones caused changes in the number of distinct leukocyte subsets, as illustrated in Fig.…”
Section: Leukocyte Numbers and Subsetssupporting
confidence: 84%
“…Despite this, there is still a traditional belief that keeping pigs in semi-dark conditions will reduce aggressiveness, even though this belief has no scientific confirmation and has been confirmed as a baseless practice [ 66 ]. Low illumination levels have been shown to impair pigs vision of object or conspecifics [ 67 ] and to increase cortisol levels [ 68 ]. Some studies have shown that providing more illumination has a positive effect on reducing competitive behaviour in finishing pigs [ 69 ] and feed activity in suckling piglets [ 16 ], although no studies have investigated the effect of light on tail and ear biting in suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced illumination has been found to reduce feed intake in pigs [ 70 ]. The reduced light exposition has shown also to influence leukocyte counts and plasma cortisol, leading possibly to a major susceptibility to diseases in finishing pigs [ 68 ]. Therefore, the present results recommend investigating the effect of illumination on piglet health and welfare.…”
Section: Discussionmentioning
confidence: 99%
“… 3 One of the characteristics of influenza infection is the elevated levels of pro-inflammatory cytokines. 9 Besides having antibacterial abilities, many antibiotics inhibits the production of pro-inflammatory cytokines specially macrolides and fluoroquinolones, which helps in reduction of cytokines level resulting in early resolution of some of the Influenza associated symptoms. 10 …”
Section: Discussionmentioning
confidence: 99%